A Study to Assess the Effectiveness of Developmental Supportive Care Bundle on Neonatal Outcomes of Low Birth Weight Babies at Selected Hospital of Ambala, Haryana - Neelam Thakur; Yogesh Kuma; Parvinder Kaur; Jyoti Sarin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Neonatal period, the first 28 days of life is most vulnerable and crucial time for babies, whose birth weight is less than 2.5 kg. Developmental supportive care is an integrated approach for these babies. The main objectives of the study were to assess and compare neonatal outcomes (physiological, comfort behavior) of LBW Babies before and after implementation of Developmental Supportive Care Bundle in experimental and comparison group and to determine the association of neonatal outcomes of LBW Babies with their selected demographic variables in experimental and comparison group. Methodology: Quasi-Experimental research design (Non- Equivalent Control Group Pretest Posttest Design) was used. Data was collected from 30 Low Birth Weight Babies (15 in each group) by convenience sampling technique in NICU of MMIMS&R of Ambala, Haryana. Pre assessment – temperature and pain assessment done before intervention in both group. After that intervention given in only experimental group and post test done on 2 to 5 days. On day 4, the mean post implementation score (36.60) of temperature was found significantly (p=.01*) higher in experimental group. On day 2 to 5, the mean post implementation score (6.80, 6.40, 6.47 and 6.47) of comfort behavior was found to be significantly (p=.006*, .001*, .005* and .002* respectively) higher in experimental group. Conclusions: The findings of the study concluded that Developmental Supportive Care Bundle (DSCB) was effective in improving neonatal outcomes (temperature and comfort behavior) of Low Birth Weight babies.